GluN2A and GluN2B N-Methyl-D-Aspartate Receptor (NMDARs) Subunits: Their Roles and Therapeutic Antagonists in Neurological Diseases - Amany Digal Ladagu; Funmilayo Eniola Olopade; Adeboye Adejare; James Olukayode Olopade (Pharmaceuticals, 2023)
N-methyl-D-aspartate receptors (NMDARs) are ion channels that respond to the neurotransmitter glutamate, playing a crucial role in the permeability of calcium ions and excitatory neurotransmission in the central nervous system (CNS). Composed of various subunits, NMDARs are predominantly formed by two obligatory GluN1 subunits (with eight splice variants) along with regulatory subunits GluN2 (GluN2A-2D) and GluN3 (GluN3A-B). They are widely distributed throughout the CNS and are involved in essential functions such as synaptic transmission, learning, memory, plasticity, and excitotoxicity. The presence of GluN2A and GluN2B subunits is particularly important for cognitive processes and has been strongly implicated in neurodegenerative diseases like Parkinson’s disease and Alzheimer’s disease. Understanding the roles of GluN2A and GluN2B NMDARs in neuropathologies provides valuable insights into the underlying causes and complexities of major nervous system disorders. This knowledge is vital for the development of selective antagonists targeting GluN2A and GluN2B subunits using pharmacological and molecular methods. Such antagonists represent a promising class of NMDA receptor inhibitors that have the potential to be developed into neuroprotective drugs with optimal therapeutic profiles.